2015
DOI: 10.1098/rsbl.2014.0947
|View full text |Cite
|
Sign up to set email alerts
|

A social insect fertility signal is dependent on chemical context

Abstract: Identifying group members and individuals' status within a group are fundamental tasks in animal societies. For ants, this information is coded in the cuticular hydrocarbon profile. We manipulated profiles of the ant Odontomachus brunneus to examine whether the releaser and primer effects of fertility signals are dependent on chemical context. Fertility status is signalled through increased abundance of (Z)-9-nonacosene (Z9 : C 29 ). Across the ant's distribution, populations have distinct hydrocarbon profiles… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
32
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 46 publications
(34 citation statements)
references
References 24 publications
2
32
0
Order By: Relevance
“…So far, studies in bumblebees have found a large amount of different substance classes such as alkanes, alkenes, aldehydes, methyl-branched alkanes, and wax-type esters to allow separation between groups (Ayasse et al 1995;Sramkova et al 2008). Furthermore, in different eusocial insects different substances seem to be driving separation between groups (e.g., Sledge et al 2001;Smith et al 2015). However, in many of the studies of eusocial insects where an influence of ovary development had been found, it was not investigated independently from possible effects like caste membership or insemination.…”
Section: Discussionmentioning
confidence: 99%
“…So far, studies in bumblebees have found a large amount of different substance classes such as alkanes, alkenes, aldehydes, methyl-branched alkanes, and wax-type esters to allow separation between groups (Ayasse et al 1995;Sramkova et al 2008). Furthermore, in different eusocial insects different substances seem to be driving separation between groups (e.g., Sledge et al 2001;Smith et al 2015). However, in many of the studies of eusocial insects where an influence of ovary development had been found, it was not investigated independently from possible effects like caste membership or insemination.…”
Section: Discussionmentioning
confidence: 99%
“…A shift toward long-chained hydrocarbons also occurs in females of the ponerine ants Pachycondyla inversa (Heinze et al, 2002) and Harpegnathos saltator (Liebig et al, 2000) and it is positively associated with fertility. Recently, it has been shown that some hydrocarbons regulate worker reproduction ("queen pheromones, " Van Oystaeyen et al, 2014), and the rest of the blend may contribute to this effect (Smith et al, 2015). Indeed, obligate social parasites take over the dominant position in social wasp colonies and their chemical signatures match that of the most dominant host female in the colony (Dapporto et al, 2004), supporting the hypothesis that the changes in the chemical signature of parasites are driven by selection for regulating worker reproduction as well as for bypassing host detection.…”
Section: Discussionmentioning
confidence: 99%
“…Phylogenetic research has revealed that O. relictus is closely related to O. brunneus, whereas O. ruginodis and O. haematodus are more distantly related but in the same New World clade (Spagna et al, 2008;Schmidt, 2009;Larabee, 2015). The cuticular chemical profiles of workers, queens and males of O. brunneus have been described previously (Smith et al, 2012(Smith et al, , 2013(Smith et al, , 2014(Smith et al, , 2015 In the laboratory, multiple colonies of each species were separately housed in two to three interconnected 60×15 mm Petri dishes with plaster-lined bottoms that were moistened twice per week. Colonies received a constant supply of water and 20% sugarwater solution, and were fed twice a week on termites and freezekilled crickets.…”
Section: Materials and Methods Study Organisms Collections And Culturementioning
confidence: 99%
“…The worker pulls its antennae away from the queen such that the antennal scape is perpendicular to the long axis of the head. This assay has been used previously in studies of fertility signal perception in O. brunneus (Smith et al, 2015).…”
Section: Bioassays Of Cuticular Extracts and Fractions Thereof Of O mentioning
confidence: 99%
See 1 more Smart Citation